Effects Due to Rhizospheric Soil Application of an Antagonistic Bacterial Endophyte on Native Bacterial Community and Its Survival in Soil: A Case Study with Pseudomonas aeruginosa from Banana - Thomas, Pious; Sekhar, Aparna C. (Frontiers in Microbiology, 2016)
Effective translation of research findings from laboratory to agricultural fields is essential for the success of biocontrol or growth promotion trials employing beneficial microorganisms. The rhizosphere is to be viewed holistically as a dynamic ecological niche comprising of diverse microorganisms including competitors and noxious antagonists to the bio-inoculant. This study was undertaken to assess the effects due to the soil application of an endophytic bacterium with multiple pathogen antagonistic potential on native bacterial community and its sustenance in agricultural soil. Pseudomonas aeruginosa was employed as a model system considering its frequent isolation as an endophyte, wide antagonistic effects reported against different phytopathogens and soil pests, and that the species is a known human pathogen which makes its usage in agriculture precarious. Employing the strain ‘GNS.13.2a’ from banana, its survival in field soil and the effects upon soil inoculation were investigated by monitoring total culturable bacterial fraction as the representative indicator of soil microbial community. Serial dilution plating of uninoculated control versus P. aeruginosa inoculated soil from banana rhizosphere indicated a significant reduction in native bacterial cfu soon after inoculation compared with control soil as assessed on cetrimide- nalidixic acid selective medium against nutrient agar. Sampling on day-4 showed a significant reduction in P. aeruginosa cfu in inoculated soil and a continuous dip thereafter registering >99% reduction within one week while the native bacterial population resurged with cfu restoration on par with control. This was validated in contained trials with banana plants. Conversely, P. aeruginosa showed static cfu or proliferation in axenic-soil. Lateral introduction of soil microbiome in P. aeruginosa established soil under axenic conditions or its co-incubation with soil microbiota in suspension indicated significant adverse effects by native microbial community. Direct agar-plate challenge assays with individual environmental bacterial isolates displayed varying interactive or antagonistic effects. In effect, the application of P. aeruginosa in rhizospheric soil did not serve any net benefit in terms of sustained survival. Conversely, it caused a disturbance to the native soil bacterial community. The findings highlight the need for monitoring the bio-inoculant(s) in field-soil and assessing the interactive effects with native microbial community before commercial recommendation.